ANALYSIS OF CONSUMER PREFERENCES IN CHOOSING PRODUCT OF TENUN IKAT KEDIRI (CASE STUDY OF TENUN MULYA KEDIRI) - Firdayanti, Febriana Kharisma; Utami, Christina Whidya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze consumer preferences toward Kediri woven ikat fabrics. The study was conducted based on inadequate corporate strategy planning data, which led to an imbalance between finished goods and goods sold. The research was carried out on Tenun Mulya products, a traditional woven fabric producer in Kediri, focusing on the attributes of color (X1), Pattern (X2), size (X3), and accessibility (X4). The color attribute consists of neutral, bright, and dark levels. The results showed that bright colors and plant-patterned Patterns had the highest preference among consumers, while the 90 cm fabric size was more favored due to its convenience in clothing production. In addition, online accessibility became the main choice for consumers in obtaining Kediri woven ikat products, in line with the development of digital technology and online shopping trends. These findings provide implications for producers in designing more efficient marketing and production strategies to enhance market competitiveness.